Asuhan Keperawatan Pada Pasien Dengan Diabetes Mellitus: Pendekatan Manajemen Glukosa Dan Edukasi Kesehatan - Mahyuvi, Tata; Djunaedi, Djunaedi (Barongko: Jurnal Ilmu Kesehatan, 2025)
Diabetes Mellitus (DM) is a chronic disease characterized by elevated blood glucose levels due to impaired insulin secretion, insulin action, or both. DM management requires a comprehensive approach involving glucose management, pharmacological therapy, lifestyle changes, and ongoing health education. This study aims to describe the implementation of nursing care for patients with DM through a glucose management and health education approach. The research design used a case study conducted on a patient with type 2 DM hospitalized in an internal medicine ward. The nursing care process included assessment, nursing diagnosis, planning, implementation, and evaluation. Interventions provided included blood glucose monitoring, nutritional management, physical activity education, foot care, and increased adherence to drug therapy. The results showed a decrease in the patient's blood glucose level from 280 mg/dL to 165 mg/dL after 5 days of intervention, improved patient understanding of DM management, and improved patient self-care skills. Health education has been shown to play a crucial role in improving self-management behaviors and reducing the risk of long-term complications.